Characterization of Plasmodium falciparum Pantothenate Kinase and Identification of Its Inhibitors From Natural Products - Nurkanto, Arif; Jeelani, Ghulam; Santos, Herbert J.; Rahmawati, Yulia; Mori, Mihoko; Nakamura, Yumi; Goto, Kana; Saikawa, Yoko; Annoura, Takeshi; Tozawa, Yuzuru; Sakura, Takaya; Inaoka, Daniel Ken; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Coenzyme A (CoA) is a well-known cofactor that plays an essential role in many metabolic reactions in all organisms. In Plasmodium falciparum, the most deadly among Plasmodium species that cause malaria, CoA and its biosynthetic pathway have been proven to be indispensable. The first and rate-limiting reaction in the CoA biosynthetic pathway is catalyzed by two putative pantothenate kinases (PfPanK1 and 2) in this parasite. Here we produced, purified, and biochemically characterized recombinant PfPanK1 for the first time. PfPanK1 showed activity using pantetheine besides pantothenate, as the primary substrate, indicating that CoA biosynthesis in the blood stage of P. falciparum can bypass pantothenate. We further developed a robust and reliable screening system to identify inhibitors using recombinant PfPanK1 and identified four PfPanK inhibitors from natural compounds.